HUBUNGAN GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN EFIKASI KOLEKTIF DENGAN KINERJA PERANGKAT KERJA DAERAH KABUPATEN BLORA - SUJANARKO , EKO (2011)
The goal of the research is to have an idea of the correlation between career commitment, job discipline, and job performance of company employees. The hypothesis put forwards by the researcher is that there is a correlation between career commitment, job discipline, and job performance of company employees. The researcher uses a quantitative correlational research model with scaling method as the data collecting technique. The researcher also uses Quota Non-random Sampling as the sample collecting technique. The location of the research is in Surakarta. The data collecting is done in three scales: the job performance scale, career commitment scale, and job discipline scale. The data analysis technique used by the researcher is Multiple Linier Regression Analysis. The result of the data analysis using Multiple Linier Regression Analysis towards the career commitment, job discipline, and job performance shows that the correlation coefficient point (r) is 0,726 and the F regression point is 33.493; p = 0,000 (p < 0,01) which means that there is certainly a very significant, linier, and strong correlation between commitment on career, job discipline, and job performance of company employees, with the effective contribution of career commitment and job discipline towards work as much as 52,8%. Besides, from the result the researcher also gains a correlation point of career commitment and job performance (rxly) as much as 45,5% and the correlation point of job discipline and job performance (rx2y) is 0,649 with the effective contribution of job discipline towards job performance as much as 42,2%. The result of the data analysis also shows that the dominant variable among the three factors is the career commitment variable (thit = 3.665) which is more influencing to the job performance than the job discipline (thit = 3.003) is.